Intonation as a Source of Information for the Creator of Choreographic Composition - Svetlana Gutkovskaya (Танцювальні студії, 2019)
The purpose of the study is to identify the levels of intonations interaction in music and choreography. Methodology. Theoretical analysis of scientific and specialized literature on the indicated problem. To identify the levels of intonation interaction in music and choreography related to the practice of composing choreographic works, such methods of scientific research as comparison, abstraction and generalization were used. Scientific novelty. The formulation of the problem of the intonations interaction in music and in choreography as applied to the field of staged activity in the field of choreographic art can be considered as being new. Information appears in this case as a specific artistic message. Conclusions. A strategy based on specific knowledge of the nature and intonation role as a source of information fundamentally changes the very approach to composing choreographic text and dance patterns. The initial thorough analysis of the intonations of the musical composition and the use of this information for selection of expressive means of choreographic composition is obligatory. The choice of expressive means by the choreographer is limited by the framework in which the musical intonation functions, as well as by the laws of interaction between music and choreography. It can be argued that musical intonations act as a carrier of very important information for the dance creator at various levels, stimulating ideas and images of the choreographic composition. The exceptions are the cases of this type of relationship of music, verbal text and choreography in works solved by means of modern dance, which are called the “mismatched” principle. The role of the performer of the choreographic text is also great, which makes the plastic intonations “convex” or levels them out.